Saccharomyces cerevisiae kinesin- and dynein-related proteins required for anaphase chromosome segregation (The Rockefeller University Press, 1995)
The Saccharomyces cerevisiae kinesin-related gene products Cin8p and Kip1p function to assemble the bipolar mitotic spindle. The cytoplasmic dynein heavy chain homologue Dyn1p (also known as Dhc1p) participates in proper cellular positioning of the spindle. In this study, the roles of these motor proteins in anaphase chromosome segregation were examined. While no single motor was essential, loss of function of all three completely halted anaphase chromatin separation. As combined motor activity was diminished by mutation, both the velocity and extent of chromatin movement were reduced, suggesting a direct role for all three motors in generating a chromosome-separating force. Redundancy for function between different types of microtubule-based motor proteins was also indicated by the observation that cin8 dyn1 double- deletion mutants are inviable. Our findings indicate that the bulk of anaphase chromosome segregation in S. cerevisiae is accomplished by the combined actions of these three motors.